A dual inertial measurement unit system for classifying standard overhead drill movements in elite women`s water polo - King, M. H.; Lewis, A.; Watson, K.; Da Costa, N.; Vicenzino, B. (Medicine & Science in Sports & Exercise, 2024)
Introduction Water polo upper limb external load monitoring cannot be currently measured accurately because of technological and methodological challenges. This is problematic as large fluctuations in overhead movement volume and intensity may affect performance and alter injury risk. Inertial measurement units (IMU) and machine learning techniques have been shown to accurately classify overhead movements in other sports. We investigated the model accuracy and class precision, sensitivity, and specificity of IMU and machine learning techniques to classify standard overhead drill movements in elite women`s water polo.